Ánalise de polimorfismo em genes ligados à força muscular em atletas de elite do atletismo brasileiro - Silva, Elton Dias da [UNIFESP] (2016)
After the end of Human Genome Project and the establishment of the complete sequence of our genetic code, scientists' interest has shifted to the analysis of variations in non-repetitive sequences present in the genome. Single nucleotide polymorphisms (SNPs), occurring on average once every 1000 bases, are the most common variations in the genome. As an general rule, SNPs have no effect on cell function, however some of them are associated with disease risk and will influence cellular responses to drugs. Study of these polymorphisms is important for several fields related to health, diagnosis and physiological behavior. SNPs can provide important information to study sports medicine and physical fitness. According to the literature, several polymorphisms of genes related to muscular, cardiovascular system and cellular metabolism affect the efficiency of expression or the protein structure encoded by these genes, resulting in greater or lesser ability to exercise. Thus the study of polymorphisms of genes involved in athletic performance becomes very important for the characterization of phenotypes linked to genetic profiles of performance for exercise, opening the possibility of developing specific traininq to achieve maximum performance. However, to assess the presence of these polymorphisms in our population, very mixed, we must also consider the frequency of a particular polymorphism in relation to their ethnic group. Thus.Jn order to obtain a genetic tool as indicative of physical performance, this study aims to investigate the polymorphisms of genes of the alpha-actinin 3, ACTN3 gene, angiotensinogen, angiotensin-converting enzyme I and B2 receptor kinins, correlated to muscle strength and endurance, through genotyping of elite athletes together with different Brazilian classical markers of ancestry.